ANALISIS KEBERHASILAN PROGRAM PERTANIAN TERPADU DI KECAMATAN PULAU SEBUKU, KABUPATEN KOTA BARU, PROVINSI KALIMANTAN SELATAN - Erni Hermanawati (Jurnal Pertanian Tropik, 2015)
Evaluation of agricultural programs is necessary to determine the level of success of an agriculturalprogram. The objective is to evaluate the research in the integrated farming program implemented infive villages in the District of Pulau Sebuku and to create a better and sustainable alternative model ofthe integrated farming application. The evaluation uses a multicriteria analysis method to make thecriteria and indicators of integrated farming principles. It can be concluded that not all of thecriteria can be accepted. Out of 10 criteria, one criterion namely environmental goals can beaccepted (with score ≥ 3) in the five villages. Two criteria namely the economic purpose and landmanagement can be accepted in four villages. The next two criteria namely social objectives andmarketing support can be accepted in two villages. Two other criteria, namely waste managementand climate/weather management can only be accepted by one village. Three criteria have notbeen acceptable to all villages, namely crop management, cattle management, and institutionalmanagement. The analysis indicates a lack of institutional function, knowledge, and technology inintegrated farming among community. Efforts to improve the program by establishing agriculturalinstitutions, human resource development as well as ease of access to saprodi and marketingfacilities. The involvement of all parties including the community, the government, the private sectorand NGOs is needed to achieve the expected success of integrated farming.